Interaction effects between food labels related to health and environmental aspects: A scoping review - Jürkenbeck, Kristin; Elsner, Rebecca; Philipsborn, Peter von; Lemken, Dominic; Schulze, Maureen (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2026)
Front-of-pack labels are widely used to communicate sustainability dimensions of foods. However, the growing number of labels raises concerns about potential interaction effects when multiple sustainability dimensions are communicated simultaneously. A scoping review was conducted to systematically map and synthesise the existing literature on consumer responses to the simultaneous presence of health-related and environmental front-of-pack labels on food products. We retrieved 7901 studies from the initial search, of which 23 met our inclusion criteria and have been included for analysis. The majority of studies applied quantitative experimental designs, primarily from Western countries. While both health and environmental labels individually tend to promote healthier and more sustainable choices, evidence on their combined effects remains inconclusive. Most studies found that two positive labels reinforce sustainable choices, whereas conflicting labels can induce compensatory inferences or confusion, potentially reducing label effectiveness. Very few studies explicitly examined conflicting dual labelling, highlighting a significant research gap. As such, it is not possible to draw general conclusions about interaction effects between health and environmental labels on foods. Overall, the findings underscore the need for systematic experimental research on dual labelling to enable general conclusions about the direction of label interaction effects.
Keywords: Food Labelling; Health Label; Environmental Label; Interaction Effect; Scoping Review; Dual Labelling; Trade-off; Consumer Behaviour